2023
DOI: 10.21037/jtd-23-387
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and toxicity of nab-paclitaxel and camrelizumab in the second or above line treatment of advanced non-small cell lung cancer: a retrospective cohort study

Abstract: Background: Paclitaxel-based chemotherapy represented by nanoparticle albumin-bound paclitaxel (nabptx) combined with programmed cell death protein 1 (PD-1)/programmed death ligand 1 (PD-L1) inhibitors has become the standard model for the 1 st treatment of advanced non-small cell lung cancer (NSCLC) with negative driver genes (such as EGFR, ALK, etc.), indicating that nab-ptx and PD-1/PD-L1 inhibitors are synergistic. Considering PD-1/PD-L1 inhibitors alone or chemotherapy single has limited efficiency in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…[ 20 , 21 ] More recently, it was found that the synergistic mechanism may lie in depleting the Treg ratio to activate an immune response. [ 22 ] Furthermore, the use of Nab-PTX plus PD-1 inhibitors has several unique benefits. For instance, the infusion conditions required for Nab-PTX or PD-1 inhibitors are simple and convenient, with no premedication requirement, decreased risk of hypersensitivity, and are important considerations for patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 , 21 ] More recently, it was found that the synergistic mechanism may lie in depleting the Treg ratio to activate an immune response. [ 22 ] Furthermore, the use of Nab-PTX plus PD-1 inhibitors has several unique benefits. For instance, the infusion conditions required for Nab-PTX or PD-1 inhibitors are simple and convenient, with no premedication requirement, decreased risk of hypersensitivity, and are important considerations for patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Nab-paclitaxel plus PD-1 inhibitor has achieved promising results in the treatment of various types of cancer ( Li et al, 2021 ; An et al, 2023 ; Sonoda et al, 2023 ; Yin et al, 2023 ; Zhang et al, 2023 ). However, clinical trials evaluating the efficacy and safety of this combination for STS treatment have not been reported.…”
Section: Introductionmentioning
confidence: 99%